Teachers' understanding of the use of Malay language oral assessment in classroom assessment - Jamil, Halimah; Md Sabil, Azhar; Mohd Kiram, Norazlina; Said, Rozita@Radhiah (Human Resource Management Academic Research Society, 2022)
Oral assessment always becomes a great challenge for teachers to assess students in the classroom. A qualitative study with a case study design was conducted to investigate teachers’ understanding on the implementation of Malay language oral assessment in classroom evaluation. The research questions in this study focus on, i) what is the definition of oral assessment based on teacher understanding?; and ii) do teachers understand how to conduct oral assessments of Malay language? Six Malay language teachers were involved in this research, with two teachers representing each of the three schools of different categories which are SMK, SABK, and SBP in one of the districts in Negeri Sembilan selected through purposive sampling. The data were collected through the triangulation method which consists of interview method, classroom observation, and analysis of related documents. The findings showed that none of the six study participants could define oral assessment as a process of interaction, which includes four forms that are parallel to DSKP and PPPBD, unable to explain all the characteristics of listening and speaking skills, and cannot properly explain oral assessment objectives. This study can give theoretical implications, allowing MOE to improve the implementation of oral assessment among teachers to more effectively achieve the goals that have been set in the KSSM assessment system.